Deglobalization and the reorganization of supply chains: Effects on regional inequalities in the EU - Glenn Magerman; Alberto Palazzolo (National Bank of Belgium, 2024)
After decades of globalization, many countries are now considering various measures to reduce their dependence on third countries and to incentivize domestic production. This paper analyzes a policy toolbox encompassing trade, industrial, and public policies and their effects on the EU and its geographical regions. We develop a multi-sector, multi-region general equilibrium framework with imperfect competition, input-output linkages, and external economies of scale. Regional and supranational governments set policies and raise taxes and provide subsidies to fund these. We calibrate our framework using detailed data on 235 EU NUTS2 regions and 25 Rest of the World aggregates, with 55 sectors and input-output linkages both within and across regions. Our results show that raising trade barriers reduces EU welfare, with substantial variation across regions. Industrial policy generates positive welfare effects. Public policy results are ambiguous. Across all policies, input-output linkages significantly amplify positive and negative welfare changes, dominating other channels such as classical gains from trade or economies of scale channels. Even common policies, like trade policy, can generate significant winners and losers across regions within the same country. Moreover, the same region can gain under one policy but lose under another. These results highlight that one policy objective can be implemented through multiple instruments, generating positive or negative aggregate welfare effects under each instrument, while obfuscating massive heterogeneity in regional outcomes, even within countries.
Keywords: F10; R12; 330; Deglobalization; Regional Inequalities; Trade policy; Industrial Policy; Public Policy; Supply Chains; General Equilibrium